The catalytic activity of cobalt nanoparticles for low-temperature oxidation of carbon monoxide. (December 2019) - Dey, S.; Dhal, G.C.
Abstract: Cobalt-based catalysts has recently noticed as a promising, noble metal-free catalyst for low temperature carbon monoxide (CO) oxidation reactions. The CO oxidation has been a huge interest in recent years because of its importance in various fields. Cobalt oxide catalysts has shown a great potential for CO oxidation catalyst in a catalytic converter for their high thermal stability and tailoring flexibility. Supported cobalt oxide nanoparticles have been synthesized over different supports at subsequent heat treatment. The cobalt oxides (Co3 O4 and CoO) can be well dispersed over supporting materials such as gamma-alumina and other covalent frameworks with average particle sizes below 5 nm. The cobalt oxide catalysts usually refer to particles of cobalt (+2 and + 3) oxide in nanometer size, with various shapes and crystal structures. In cobalt oxide catalyst presence of Co 3+ /Co 2+ redox couple with oxygen vacancy formation. Under steady-state conditions, the Co3 O4 surface appeared with oxidized Co 2+ species. Activity order of CO oxidation over various cobalt nanoparticles was observed as follows: nanoplates > nanorods > nanocubes > nanosphere. Cobalt has been reported as a good catalyst from economic, thermal, activity, selectivity, and availability point of view. There are various mechanisms that have been developed in the analysis of CO oxidation reaction over cobalt oxide catalysts. These mechanisms are reliable and good enough as per the current situation in the literature. This manuscript provides a summary of published information regarding pure and substituted cobalt oxide catalyst, synthesize methods, and their application for CO emissions control. Highlights: Cobalt-based catalyst is considered as an attractive alternative to the noble metals because of its lower cost, abundant availability, and higher activity at low temperature for total oxidation of carbon monoxide (CO). In Co3 O4 catalyst the Co 3+ cations located at the octahedral sites, and Co 2+ cations located at the tetrahedral sites. The Co 3+ cations play an important role for oxidation of CO. The Co3 O4 nanosheets contain high concentrations of Co 3+, abundant adsorbed oxygen species, high reducibility, and superior oxygen desorption capacity.